The Role of Body Shame in Sexual, Relationship, and Life Satisfaction in Women. Issue 1 (2nd January 2020) - McLean, Lauren L.; La Guardia, Amanda C.; Watts, Richard E.; Nelson, Judith
ABSTRACT: The purpose of this study was to measure how body shame, sexual satisfaction, and relationship satisfaction predicted life satisfaction for female participants who have been in committed relationships for at least a year and who have engaged in sexual activity with their partners (N = 138). Researchers examined data to determine how body shame may interact with: (a) sexual satisfaction, (b) relationship satisfaction, and (c) life satisfaction. Results indicate that body shame and relationship satisfaction account for the greatest amount of variance in life satisfaction for the respondents.